Effects of Nanoparticles on Double-Stranded RNA Stability in Moth Hemolymph - Parks, Lina; Cooper, Anastasia; Song, Huifang; Yu, Zhitao; Zhang, Hao; Silver, Kristopher; Zhang, Jianzhen; Zhu, Kun Yan (My University, 2018)
RNA interference (RNAi) is an immune response in which double-stranded RNA (dsRNA) suppresses a target gene. By designing dsRNA to target genes that are necessary for life, dsRNA can potentially be used as an insecticide. RNAi-based insecticides are badly needed because they are more specific than conventional pesticides and because many insects have developed resistance to pesticides. Unfortunately, some insects produce enzymes that degrade dsRNA and prevent the RNAi response (Cooperet al., 2018). Therefore, RNAi-based insecticides currently cannot be used to control all insects. Here we investigate dsRNA stability when incubated in hemolymph ex vivoto determine if degradation of dsRNA is contributing to the inadequate RNAi response exhibited by lepidopterans, such as the European corn borer (ECB, Ostrinia nubilalis). Our findings indicate that dsRNA is significantly degraded in ECB hemolymph, but encapsulation of dsRNA in chitosan-based nanoparticles (CB-NPs) enhances stability. These findings provide insight into RNAi efficiency limitations in insects, and may provide a method to enhance RNAi efficiency in lepidopterans and other RNAi-refractory pests.
Keywords: Fall 2018